Unraveling the role of LINC02657 in clear cell renal cell carcinoma: insights into tumor aggression, immune modulation, and treatment response - Tong, Juncheng; Liu, Yang; Tang, Aifa; Xiong, Xiangguo; Liu, Lifang; Fan, Zhenqing; Qian, Cheng; Mei, Hongbing; Wang, Han (Frontiers in Immunology, 2026)
BackgroundThe role of long non-coding RNA LINC02657 in clear cell renal cell carcinoma (ccRCC) is poorly defined. This study aims to characterize its expression, clinical relevance, and oncogenic functions in ccRCC.MethodsWe analyzed LINC02657 expression in pan-cancer and ccRCC cohorts from TCGA and ICGC. Prognostic value for overall (OS) and disease-specific survival (DSS) was evaluated using Kaplan-Meier and multivariate Cox regression. Functional mechanisms were investigated via Gene Set Enrichment Analysis (GSEA) and in vitro assays in 786-O and ACHN cells following LINC02657 knockdown, assessing proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT). Drug sensitivity analysis was conducted using the GDSC2 database.ResultsLINC02657 was significantly upregulated in ccRCC tissues. High LINC02657 expression predicted poorer OS and DSS and was an independent prognostic factor for adverse outcomes. GSEA linked it to cell cycle regulation and mitotic checkpoint signaling. Functional experiments demonstrated that LINC02657 knockdown effectively inhibited ccRCC cell proliferation, migration, and invasion, and promoted reversal of EMT toward an epithelial phenotype. Additionally, its expression was associated with immune cell infiltration and checkpoint molecule levels. Drug sensitivity profiling indicated that low LINC02657 expression enhanced sensitivity to chemotherapy agents, including docetaxel, gemcitabine, and 5-fluorouracil.ConclusionsLINC02657 is a critical oncogenic lncRNA in ccRCC, promoting tumor progression by regulating cell cycle, EMT, and immune microenvironment. It serves as a robust independent prognostic biomarker and a potential therapeutic target, offering valuable insights for personalized ccRCC treatment strategies.